ANALISIS FAKTOR RISIKO KELUHAN NYERI PUNGGUNG BAWAH MENGGUNAKAN SOFTWARE CATIA PADA PEKERJA BAGIAN PERMESINAN DI UMKM SAESTU MAKARYO, PATI - Novi Tristiawan; Ida Wahyuni; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The process of metal machining is one of the processes in making a product by changing desired shape of the metal. Based on carrying out observations the work activities found awkward body posture that was bending. From the interview results found that lower back pain most common complained among workers. The purpose of this study was to analyze the risk factors for complaints of lower back pain in machining activity workers at UMKM Saestu Makaryo, Pati. This study used quantitative with analytic observational and cross sectional research approach. The subjects of this study were all Saestu Makaryo's UMKM machinery activities workers as much as 33 people with total sampling method. Data retrieval is done by observing work posture and RULA analysis using CATIA software to assess awkward posture and action recommendations for workers' awkward posture in the form of correct sitting posture, as well as filling in the Visual Analogue Scale (VAS) sheet for complaints of lower back pain. The results of data analysis using Chi Square and Fisher's Exact Test metod found a correlation between working period (p=0.017) and posture (p=0.033) with complaints of lower back pain. There was no correlation between age (p=0.339) and gender (p=0.618) with complaints of lower back pain complaints on machining activity workers. It is recommended for business owners to improve the design of the workplace and to socialize the right sitting posture to workers. Factors that cause no relationship between complaints of lower back pain with age are caused by other factors outside the study, namely the rest. There is no relationship between the variables of complaints of low back pain with gender due to variables outside the research namely exercise habits.